Kajian Pengaruh Sistem Kekerabatan pada Persepsi Yudisial dalam Menangani Kasus Kekerasan Terhadap Perempuan - Enny Ristanty (University of Merdeka Malang, 2018)
Research focuses on the study of one component of the legal system, namely the aspect of legal culture. There are indications that Judge’s decisions that are very diverse sometimes do not reflect a sense of justice. The values adopted by the Judges turned out to have an influence on their perceptions in giving decisions on cases of violence against women. 4 judges prioritized a sense of justice in their verdict, 1 judge chose the element of legal benefit, 1 judge chose legal certainty and 3 judges said all elements were prioritized. While the equality of all judges with different backgrounds from different kinship uses the norms for legal certainty. The internal and external legal culture factors of judges that have a significant impact on decisions in cases of violence still need to be examined more deeply in terms of questions,the material proposed should be more specifically exploring non-legal aspects using a legal psychology approach. 4. The impact of the kinship system on the perceptions of the judges of the decision specifically to contribute in cases of domestic violence can actually contribute significantly to the legal aspects of culture in Indonesia.How to cite item: Ristanty, E. (2018). Kajian Pengaruh Sistem Kekerabatan pada Persepsi Yudisial dalam Menangani Kasus Kekerasan Terhadap Perempuan. Jurnal Cakrawala Hukum, 9(2), 127-134. doi:https://doi.org/10.26905/idjch.v9i2.2765